INHERITANCE LAW IN SPAIN - Stanislav Medvedev (Гуманитарные и юридические исследования)
The article considers the peculiarities of the Spanish law of succession: it is represented in the Civil Code of Spain as a way of acquiring property rights, the major role in the succession law plays the local law on autonomous unities, more democratic in establishing the age of testamentary capacity, more democratic addressed the issue of conversion of the will, drawn up in extraordinary circumstances, than in the Russian law, the obligatory share heirs up to 2/3 of the estate among the heirs mandatory stands «the best compulsory heir», recognized heirs to 4-degree relatives, while according to the Russian law, including 7 degree. All these features make it possible to compare with the Russian law of succession, and to borrow from the Spanish inheritance law useful and suitable provisions for the improvement of our institution of inheritance.